ADOPTION OF 4.0 TECHNOLOGIES IN AGRICULTURE: PROPOSITION OF A PROCESS BASED ON CASE STUDIES IN BRAZIL - Santos, Isabela Gaya; Soares, Bruno Jorge; Dias, Eduardo Mario; Scoton, Maria Lídia Rebello Pinho Dias; Menezes, José Henrique Videira; Oliveira, Diego Humberto de (REVISTA DE AGRICULTURA, 2023)
4.0 technologies have been adopted in several sectors, such as the agricultural sector. In Brazil, recent research showed that around 50% of farmers adopt precision agriculture technologies, indicating opportunities for diffusion in the country. This work aimed to identify a process flow for the adoption of 4.0 technologies in agriculture, based on a case study carried out in 14 pilot projects of the Agro 4.0 Program of the Brazilian Agency for Industrial Development - ABDI, carried out in Brazil between 2020 and 2022. The study was carried out through the application of questionnaires and interviews with those responsible for the projects and in the consolidation of a flowchart. As a result, it was possible to understand elements that characterize the context of 4.0 technologies adoption, such as motivations, challenges and critical factors, in addition to identifying processes and sub-processes for this challenge. Â 